A function-based linear map symbol building and rendering method using shader language. Issue 2 (1st February 2016) - Yue, Songshan; Yang, Jianshun; Chen, Min; Lu, Guonian; Zhu, A-xing; Wen, Yongning
Abstract : Maps are widely used to visualize geo-information so that map users can develop related understandings about the real world. Such a process for communicating information is largely dependent on the rendering of map elements using different symbols (points and linear and area symbols). To meet the demand of more dynamic and comprehensive visualization in map rendering, it is essential to improve the rendering efficiency. This paper focuses on these research topics, especially the difficulty in constructing and drawing linear map symbols. By employing shader language, a function-based linear symbol building and rendering method is presented in this paper. The basic idea of this function-based method is to build a map-rendering solution that employs graphic processing unit (GPU) acceleration technology to improve the rendering efficiency. A 'function' is used to represent the algorithm that draws certain simple or complex linear map symbols. This function reflects the structure of a linear map symbol (describing the symbol construction information) and also the rendering process of the symbolized linear map elements (handled on a per-pixel basis by the shader program). Based on the Open Geospatial Consortium (OGC), Styled Layer Descriptor (SLD) specifications, four basic line types (i.e., solid lines, dashed lines, gradient color lines, and transition lines) are implemented in the proposed method, and the implementation of line markers, line joins and line caps is also discussed. Three experiments are conducted to demonstrate improvements in map rendering. The results show that a variety of linear map symbols can be constructed in a uniform way, which suggests that the proposed method addresses the difficulty in drawing linear map symbols. With this method, the efficiency of rendering linear map elements is substantially improved compared to using the graphics device interface plus (GDI+) and anti-grain geometry (AGG) methods; it also provides an applicable approach for developing map rendering systems. Using this function-based concept, the complexity of building linear map symbols and drawing linear map elements can be decreased.